Disentangling multiple relationships of species diversity, functional diversity, diatom community biomass and environmental variables in a mountainous watershed - Liu, Chan; Sun, Tingting; Wu, Xuan; Tan, Lu; Cai, Qinghua; Tang, Tao (Frontiers in Ecology and Evolution, 2023)
Abstract Biodiversity and ecosystem functioning (BEF) relationships are important research issues in the context of biodiversity loss. However, most studies only explored BEF relationships using species richness as a proxy for biodiversity without considering the effects of species evenness and importance of functional diversity on ecosystem functioning. In the present study, we explored multiple relationships among in-stream environmental variables, species diversity (species richness and species evenness), functional diversity (functional richness, functional evenness and Rao's quadratic entropy index) and biomass of benthic diatom communities from a Chinese mountainous river network. We tested two hypotheses: (1) species richness and evenness affect community biomass independently, and (2) species diversity directly affects community biomass and also indirectly affects community biomass by influencing functional diversity. We found that benthic diatom diversity and biomass were influenced by wetted width, conductivity, and pH. Species richness and evenness had positive and negative effects on community biomass, respectively; while, the effect of richness (with a pathway coefficient of 0.39) was stronger than that of evenness (-0.28). However, we have not found an interaction pathway between species richness and species evenness in structural equation models, indicating that the two effects on community biomass were independent of each other. Both functional richness and Rao's quadratic entropy index had positive effects on community biomass, although effects of other variables blurred the relationship between functional richness and community biomass in structural equation modeling. Besides direct effects, species diversity also indirectly affected community biomass through influencing Rao's quadratic entropy index, with direct effects (0.27) were more than twice stronger than indirect effects (0.12). Our findings imply that the selection effect played a dominant role in the relationship between diatom diversity and biomass, indicated by the negative species evenness and biomass relationship; meanwhile, the complementarity effect was also important. The inclusion of more diversity indices to explore the biodiversity-biomass relationship would help to provide a deeper and more comprehensive understanding of this relationship and its driving mechanisms. We suggest carrying out more studies on BEF relationships in streams and rivers to support protection practices for sustaining biodiversity and their ecosystem functions in natural lotic ecosystems.